PENERAPAN MODEL NUMBER HEAD TOGETHER DALAM MOTIVASI DAN HASIL BELAJAR MATA KULIAH BAHASA INGGRIS UNTUK MEMPERSIAPKAN SDM UNGGUL - Aly Imron; Mujianto Mujianto; Yani Ratnawati (Politeknik Negeri Malang, 2019)
The objective is to know the increase of students learning motivation and students outcome through implementation of cooperative learning with Numbered Heads Together method of the English subject. This experimental research is using designing Classroom Action Recearch by applying qualitative approach as well as it is conducted in two cycles in which it involves planning, action, observation, and reflection. The result that the comparison result of students between the first and second cycles is significant and rise sharply, meaning that, second cycles is quite good seen from students’ motivation consisting of Interest (57.33%; 88) %, concentration (62.67%; 92%), attention (56%; 85,33%), perseverance (61,33%; 87,33%). The average increase is 26% from the first to 2nd cycles.